Ecologically Sustainable N‑doped Graphene Nanosheets as High-Performance Electrodes for Zinc–Air Batteries and Zinc-Ion Supercapacitors - Das, Gouri Sankar; Tripathi, Kumud Malika (ACS applied electronic materials, 2024)
The development of low-cost, green, durable, and high-performance electrocatalysts that accelerate the sluggish kinetics of the oxygen evolution and reduction reactions in metal–air batteries is a subject of intense research. Multifunctional nitrogen-doped graphene nanosheets (N-GNS) with impressive electrochemical performance for applications in rechargeable Zn–air batteries (ZABs) and Zn-ion supercapacitors (ZISCs) have been synthesized by a scalable facile pyrolysis method using chickpea as the raw material. Benefiting from the structural functionalities, synergistic effect between N-doping and oxygenated functional groups, high electrical conductivity, and availability of high density of catalytically active sites for ion reactions, the resultant N-GNS exhibited enhanced kinetics for the oxygen evolution/reduction reactions and high electrochemical performance. The rechargeable ZABs with N-GNS-based air cathode exhibited excellent cycling stability of 100 h@10 mA cm–2 discharge current and a comparable open circuit voltage (1.43 V) and provided a peak power density of 96 mW cm–2. Moreover, the electrocatalytic performance of N-GNS was almost similar to that of expensive platinum for stable open circuit voltage. In addition, the N-GNS cathode in ZISCs delivered a specific capacitance of 291 F g–1 at 0.1 A g–1 current density. The capacity retention in hybrid devices was 86% with 100% Coulombic efficiency after 10,000 charge–discharge cycles at 10 A g–1. N-GNS acts as a dual-functional electrode in Zn–air batteries and Zn-ion supercapacitors, providing opportunities for green power sources, especially for portable electronics.